Effect of social media influencers on purchase intentions of Saudi Arabia consumers: instagram as an evaluation tool - Al-Nasser, Asem; Bali Mahomed, Anuar Shah (IAEME Publication, 2020)
The role of Influencer marketing as an emerging marketing form can never be over-emphasize whereby a business is conducted through platforms of social networks such as Twitter, Instagram, WhatsApp, Facebook and many other social media tools as a carrier for social sharing about products or vendors to persuade interest in a product, thus increasing the rate of purchase intention of the customers. Presently, Social Media Influencers (SMIs) are gaining popularity globally, due to their credibility, persuasiveness and professionalism impact on purchase intention of consumers. This review examines customers' engagement and evaluation of products via SMIs on Instagram as well as the role played by SMIs in influencing buyers purchasing decisions. Interestingly, this review establishes a unique feature of Instagram about products that make Instagram a significant evaluation tool for customers searching for additional information about new products. Thus, within a very short period, it's common for ordinary people on Instagram to become influencers and celebrities. Lastly, implications and recommendations for future research associated with SMIs' impact on purchase intentions of Instagram users using Instagram as a tool of evaluation in the kingdom of Saudi Arabia were also highlighted.